The Implementation of Post-Pandemic Blended Learning in Elementary Schools - Waruwu, Nurdelima; Arifin, Fatkhul; Hady, Yazid (Tafkir: Interdisciplinary Journal of Islamic Education, 2023)
This study aims to analyze the implementation of post-pandemic blended learning in elementary schools at Jabodetabek. We know that for two years, learning has always been done with a remote system using the e-learning method. In the new normal era, learning began to be integrated with a blended system, namely a combination of face-to-face and remote. There are also those who mean combining two methods, namely conventional methods, and e-learning. The method used is a survey research method with a descriptive approach, where researchers identify the uses of blended learning in learning and conduct management analysis of the application of blended learning at the MI/SD level after the Covid-19 pandemic. The research was conducted in 2021 in the Jabodetabek area. The instrument used is a questionnaire supported by theory and observations. In the research results obtained from 186 respondents, 82% stated that the application of post-Covid 19 blended learning in elementary schools was still relevant. So the researchers concluded that blended learning is a new method of learning. Class is not the only place for learning, teachers can do learning anywhere and anytime.